Просодическая природа латышского консонантизма - Brēde, Maija; Gurtaja, Valentīna (Baltistica, 1989)
PROSODIC CHARACTERISTICS OF CONSONANTS IN LATVIAN The prosodie characteristics of a group of voiceless noise consonants and sonants (duration, intensity, frequency) have been examined in the phonetic context, depending on the sound position in a word (initial, medial, final) and the word position with a corresponding consonant in a phrase. Duration and intensity depend (a) on the manner of the consonant production: the longest and most intensive are affricates, constrictives and occlusive nasal sonants; (b) on the place of the consonant production: the longest and most intensive are forelingual dental noise consonants and the bilabial sonant; (c) on positional factors. The sonant duration is related to the type of syllabic accent. The parameters of the sonant frequency show a relatively little dependence on positional factors.